ChemInform Abstract: Catalytic Formation of Monosaccharides: From the Formose Reaction Towards Selective Synthesis. Issue 43 (21st October 2014) - Delidovich, Irina V.; Simonov, Alexandr N.; Taran, Oxana P.; Parmon, Valentin N.
Abstract Review: [110 refs.